2009
DOI: 10.1074/mcp.m800588-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Proteomics Analysis of the Human Kinome

Abstract: Members of the human protein kinase superfamily are the major regulatory enzymes involved in the activity control of eukaryotic signal transduction pathways. As protein kinases reside at the nodes of phosphorylation-based signal transmission, comprehensive analysis of their cellular expression and site-specific phosphorylation can provide important insights into the architecture and functionality of signaling networks. However, in global proteome studies, low cellular abundance of protein kinases often results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
232
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(246 citation statements)
references
References 47 publications
14
232
0
Order By: Relevance
“…Membrane Translocation-To explore the mechanism by which API-1 inhibits Akt, we performed a protein kinase-compound binding assay because API-1 contains an amino group that has been shown to bind to NHS-activated Sepharose (22)(23)(24). After immobilization, compound-bound Sepharose beads were incubated with recombinant Akt protein.…”
Section: Api-1 Directly Binds To Akt Protein and Inhibits Aktmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane Translocation-To explore the mechanism by which API-1 inhibits Akt, we performed a protein kinase-compound binding assay because API-1 contains an amino group that has been shown to bind to NHS-activated Sepharose (22)(23)(24). After immobilization, compound-bound Sepharose beads were incubated with recombinant Akt protein.…”
Section: Api-1 Directly Binds To Akt Protein and Inhibits Aktmentioning
confidence: 99%
“…The assay for API-1 binding to Akt was performed essentially as previously described for other kinase inhibitors that contain an amino group (22)(23)(24). API-1 was immobilized on Sepharose beads (GE Healthcare) through covalent linkage using its amino group (Fig.…”
Section: Api-1 and Akt Protein Binding Assay-mentioning
confidence: 99%
“…S778 is located in a canonical PKA phosphorylation site and mutation of either S778 or the two basic residues involved in kinase interaction resulted in GFPPyk2 700-841 nuclear relocalization. Large-scale analysis of protein phosphorylation using mass spectrometry has found that S778 is one of the phosphorylated residues of Pyk2 in vivo [47,48]. However, until now, nothing was known about the specific function of S778 and this is the first time a role of Pyk2 S/T phosphorylation has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to Cdc7 autophosphorylation 14 or phosphorylation by other kinases such as polo-like kinase (Plk), as large scale proteomics studies indicated that Plk phosphorylates Cdc7 at Serine 27 and 277 in prometaphase. 26,28,[30][31][32][33] In any event, our data demonstrate that Cdc7 is phosphorylated at multiple sites in a mitotic Cdkdependent manner around prometaphase.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependementioning
confidence: 91%